Morphogenesis of Influenza A Virus in Ehrlich Ascites Tumor Cells as Revealed by Thin-Sectioning and Freeze-Etching - Bächi, T. (1969)
The budding of a tumor-adapted strain of influenza A(0) virus at the surface of Ehrlich ascites tumor cells was studied by electron microscopy. Thin sections of budding sites showed the formation of a fuzzy coat on the outside of the cell membrane and simultaneously the apposition of a dark layer on the inner side. The continuity of cellular and viral membrane seemed to be preserved up to the point where the virion remained attached by only a thin stalk. Freeze-etching of virus budding sites yielded pictures in which a clear differentiation between the viral membrane and the host cell membrane was visible. The breaks across the fuzzy coat revealed striations corresponding to the “spikes” seen in negative contrast, whereas tangentially broken virus particles were best interpreted by assuming that splitting occurred midway between the two outer layers of the envelope.